Correlation between Vegetable Consumption Behavior During Pregnancy and Perineal Elasticity of Mothers Giving Birth at Sungai Lulut Midwife Independent Practice in 2022 - Aulia Rahmi (Jurnal EduHealth, 2023)
Based on the experience of researchers when sewing perineal wounds in childbirth, it was found that there was a dense and elastic perineum, from the results of brief interviews with patient behavior during pregnancy. Of the 10 mothers who gave birth with the perineum stitched and the perineum was dense and elastic, there were similarities in behavior, namely they like to eat green vegetables . The research method in this study used a cross-sectional approach, this type of research was a quantitative study. The population in this study were all birth mothers who were recorded in the Sungai Lulut Midwife Independent Practice register from July to December 2022 totaling 33 respondents. The sample technique used was with the total sampling method, the data analysis used was univariate and bivariate analysis, with the Chi Square statistical test (confidence level 0.05). The research results show that the p value is 0.03, thus the p value is less than 0.05, so Ho is rejected and Ha is accepted. The conclusion is that there is a significant relationship between Vegetable Consumption Behavior During Pregnancy and the Elasticity of the Perineum of Maternity Mothers in Sungai Lulut Midwife Independent Practice in 2022